The Influence of the Direct Method on Students' Language Comprehension: Quantitative Research with a Focus on Listening Skills - Rizky Wardhani; Haris Danial; Delsa Miranty; Ariana Oktaviana; Nining Fitriani (International Journal of Language and Ubiquitous Learning, 2024)
Background. The Direct Method has become an attractive approach in language learning, emphasising the use of the target language in communicative situations. However, the impact of the Direct Method on students' language comprehension, particularly in listening skills, still needs to be studied in depth. Purpose. This study aims to evaluate the effect of the Direct Method on students' language comprehension, focusing on listening skills in the context of English language learning. Method. A quantitative approach was used to analyse data from the listening comprehension scores of students who took the Direct Method. The research sample consisted of 100 students who took the Direct Method course. Results. The results showed that the Direct Method had a positive and significant influence on students' listening comprehension ability. Of the 100 students who took the course with the Direct Method, 85% showed a significant improvement in listening comprehension scores. Conclusion. In the context of English language learning, the Direct Method has great potential in improving students' listening comprehension. This approach provides an interesting and meaningful learning experience for students, allowing them to be actively involved in the learning process and improving their ability to understand and use the target language.